Discovery of a novel B-cell lymphoma 6 (BCL6)–corepressor interaction inhibitor by utilizing structure-based drug design. Issue 17 (1st September 2017) - Yasui, Takeshi; Yamamoto, Takeshi; Sakai, Nozomu; Asano, Kouhei; Takai, Takafumi; Yoshitomi, Yayoi; Davis, Melinda; Takagi, Terufumi; Sakamoto, Kotaro; Sogabe, Satoshi; Kamada, Yusuke; Lane, Weston; et al.
Graphical abstract: Abstract: B-cell lymphoma 6 (BCL6) is a transcriptional repressor that can form complexes with corepressors via protein–protein interactions (PPIs). The complexes of BCL6 and corepressors play an important role in the formation of germinal centers (GCs), and differentiation and proliferation of lymphocytes. Therefore, BCL6–corepressor interaction inhibitors would be drug candidates for managing autoimmune diseases and cancer. Starting from high-throughput screening hits1a and2a, we identified a novel BCL6–corepressor interaction inhibitor8c (cell-free enzyme-linked immunosorbent assay [ELISA] IC50  = 0.10 µM, cell-based mammalian two-hybrid [M2H] assay IC50  = 0.72 µM) by utilizing structure-based drug design (SBDD) based on an X-ray crystal structure of1a bound to BCL6. Compound8c also showed a good pharmacokinetic profile, which was acceptable for both in vitro and in vivo studies.